2004
DOI: 10.1038/ncb1131
|View full text |Cite
|
Sign up to set email alerts
|

Functional proteomic screens reveal an essential extracellular role for hsp90α in cancer cell invasiveness

Abstract: Tumour cell invasiveness is crucial for cancer metastasis and is not yet understood. Here we describe two functional screens for proteins required for the invasion of fibrosarcoma cells that identified the molecular chaperone heat shock protein 90 (hsp90). The hsp90 alpha isoform, but not hsp90 beta, is expressed extracellularly where it interacts with the matrix metalloproteinase 2 (MMP2). Inhibition of extracellular hsp90 alpha decreases both MMP2 activity and invasiveness. This role for extracellular hsp90 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
498
1
7

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 551 publications
(527 citation statements)
references
References 41 publications
21
498
1
7
Order By: Relevance
“…Previously, secretion of HSP90a into the extracellular matrix surrounding tumour cells was reported to assist the activation of MMP-2 as well as contributing to tumour cell invasiveness [20,21]. We show that Hop is found in the conditioned medium of both Panc-1 and BxPc-3 cells and therefore may possibly have an extracellular role in Hsp90 client protein activation (Fig.…”
Section: Matrix Metalloproteinases Down Regulated As a Results Of Hop mentioning
confidence: 68%
“…Previously, secretion of HSP90a into the extracellular matrix surrounding tumour cells was reported to assist the activation of MMP-2 as well as contributing to tumour cell invasiveness [20,21]. We show that Hop is found in the conditioned medium of both Panc-1 and BxPc-3 cells and therefore may possibly have an extracellular role in Hsp90 client protein activation (Fig.…”
Section: Matrix Metalloproteinases Down Regulated As a Results Of Hop mentioning
confidence: 68%
“…In this study, we revealed that vibsanin B preferentially targets HSP90b and has a very weak binding with HSP90a through activity-based protein profiling method (40), indicating that inhibition of HSP90b, but not HSP90a, would be mainly responsible for the inhibitory effect of vibsanin B on leukocyte migration. Because of high conservation in sequence, the function of HSP90a and HSP90b is very similar (41), although previous work reported that HSP90a, but not HSP90b, exerts an essential extracellular role in cancer cell invasiveness (42). At the level of structural biology, the HSP90 monomer contains three separate domains: the N-terminal domain, middle domain, and carboxyl-terminal domain, all of which bind different molecules to form functional HSP90 chaperone machinery (41).…”
Section: Discussionmentioning
confidence: 99%
“…Hsp70, Hsp90) are present in human plasma and CSF and are associated with cell surfaces (in particular cancer cells); they are thought to be released from dead or dying cells. Many potentially important extracellular roles have been proposed for these chaperones, such as cancer cell invasiveness (Eustace et al, 2004), immune presentation (Becker et al, 2002) and signaling (Whittall et al, 2006). However, these "normally intracellular" chaperones are present extracellularly at very low (ng/ml) levels and require ATP to carry out protein refolding.…”
Section: Extracellular Chaperonesmentioning
confidence: 99%